Rereading Nepal’s Language Diversity and Ethno-Linguistic Movements in Tarai-Madhesh - Gautam, Bhim Lal (Nepal Journal of Sociology, 2025)
This argumentative essay aims to initiate discussion, emphasizing the dynamics of language and identity politics in Nepal, particularly focusing on the period following the political shift in 1990 and the political transitions that developed after 2006. The essay inquires how and why languages are being hyped and pushed forward as a primary means within the identity movement. However, in daily life, linguistically, all languages and their dialects, including Nepali, have waxed and waned over time, transforming into an odd and unusual form. Moreover, it also poses a challenge to use them all within the diverse multilingual landscape of Nepal, where their populations are dispersed across various mixed communities. To illustrate, the essay revolves around two opposing cases of ethno-linguistic movements, specifically the Madheshi and T haru, situated in the central Tarai region of Nepal and delves into issues concerning social inclusion, ethno-cultural recognition, political representation and the ensuing political dynamics.